2012
DOI: 10.1128/jcm.01205-12
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR for Diagnosing Helicobacter pylori Infection in Patients with Upper Gastrointestinal Bleeding: Comparison with Other Classical Diagnostic Methods

Abstract: The aim of this study was to determine the diagnostic usefulness of quantification of the H. pylori genome in detection of infection in patients with upper gastrointestinal bleeding (UGB). A total of 158 consecutive patients with digestive disorders, 80 of whom had clinical presentation of UGB, were studied. The number of microorganisms was quantified using a real-time PCR system which amplifies the urease gene with an internal control for eliminating the false negatives. A biopsy sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
1
39
0
5
Order By: Relevance
“…Lower sensitivity for HpSA is also shown in patients with upper GI bleeding. 24 In order to limit these possibilities, we excluded GI bleeding patients as well as patients with diarrhea which makes our results more accurate. However, the limitation of the study was the small number of cases.…”
mentioning
confidence: 99%
“…Lower sensitivity for HpSA is also shown in patients with upper GI bleeding. 24 In order to limit these possibilities, we excluded GI bleeding patients as well as patients with diarrhea which makes our results more accurate. However, the limitation of the study was the small number of cases.…”
mentioning
confidence: 99%
“…It has been also reported that Real-time PCR can improve H. pylori detection rate in a histology-negative, formalin-fi xed, and paraffi nembedded tissue [ 33 ]. Since the newly developed quantitative real-time PCR is around ten times more sensitive than the conventional PCR method [ 34 ], real-time PCR in diagnosis of H. pylori infection in patients with UGI bleeding could be useful diagnostic methods with increase in sensitivity and additional gain of bacterial load [ 35 ]. However, further study about the cut-off value which can distinguish the real infection from asymptomatic colonization is warranted.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 97%
“…Desde hace muchos años se han utilizado métodos moleculares caseros para el diagnóstico de la infección por H. pylori a partir de diferentes muestras como biopsia gástrica, heces, saliva, jugo gástrico, etc. Además, permiten el estudio de mutaciones de resistencia a macrólidos como claritromicina (gen 23S ARNr), fluoroquinolonas (gen gyrA), tetraciclinas (gen 16S ARNr), rifabutina (gen rpoB) y amoxicilina (gen pbp-1a) 41,42 , y tienen las ventajas de la rapidez, de la mayor sensibilidad que el cultivo con métodos fenotípicos de sensibilidad a antibióticos, y detectan resistencia heterogénea, que puede ser difícil de obtener por cultivo 39,43 .…”
Section: Helicobacter Pyloriunclassified